Making EU-Turkey cooperation on migration sustainable: A greater focus on the Turkish host society is required - Sinem Adar; Friedrich Püttmann (Stiftung Wissenschaft und Politik (SWP), 2022)
Managing irregular migration is a focal point of EU-Turkey relations today. European perspectives on this issue, for the most part, are split into two camps: a 'caring' one, which concentrates on the well-being of refugees, and a 'concerned' one, which focusses on the external border security of the European Union (EU) and the anxieties of EU citizens. Widely overlooked in the European discussions is the mounting social and political discontent in Turkey, which is hosting the largest refugee population worldwide while facing a serious economic crisis alongside a severe governance deadlock. To bear fruits in the long run, any EU-Turkey migration cooperation should account for this growing discontent. After all, neither the advancement of the rights of refugees in Turkey nor reliable security cooperation is possible without accord by the Turkish political class and society. To this end, the EU should signal to Turkey its intention to resettle more refugees and support local integration efforts more proactively.
Keywords: 320